2009
DOI: 10.1380/ejssnt.2009.878
|View full text |Cite
|
Sign up to set email alerts
|

Incident Angle Dependence in Polymer TOF-SIMS Depth Profiling with C60 Ion Beams

Abstract: Cluster ions such as C + 60 are well used as the sputtering ions for polymer depth profiling. The molecules of analyte surfaces are occasionally damaged by the ion bombardment during sputtering, leading to a loss of the molecular information. In order to obtain a proper polymer depth profile, sputtering conditions shall be optimized, however, they have not been investigated sufficiently. In this study, incident angle dependence was investigated at the angle from 48• to 76• with respect to the surface normal. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0
1

Year Published

2010
2010
2013
2013

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 13 publications
2
9
0
1
Order By: Relevance
“…[4] Recently, incident angle dependences for C 60 bombardment on polymer samples were investigated by SIMS experiments and molecular dynamics simulations in other groups. [20,21] These results indicated that the damage of samples was suppressed by the bombardment at grazing angle of incidence, which are basically in agreement with our results. However, the emitting behavior of huge molecules such as proteins has been firstly characterized in this study.…”
Section: Methodssupporting
confidence: 92%
“…[4] Recently, incident angle dependences for C 60 bombardment on polymer samples were investigated by SIMS experiments and molecular dynamics simulations in other groups. [20,21] These results indicated that the damage of samples was suppressed by the bombardment at grazing angle of incidence, which are basically in agreement with our results. However, the emitting behavior of huge molecules such as proteins has been firstly characterized in this study.…”
Section: Methodssupporting
confidence: 92%
“…The reference materials have already provided insight into fundamental aspects of organic depth profiling, such as the dose and energy dependence of the sputtering yield, the depth resolution, sputter‐induced roughening and molecular secondary ion behavior. This study has enabled new approaches to organic depth profiling to be quantitatively tested, including sample rotation,19 cooling,19, 22, 23 low incidence impact angles18, 24 and bevels,20, 25 and also shown that the repeatability and reproducibility of most aspects of organic depth profiling is excellent.…”
Section: Introductionmentioning
confidence: 94%
“…This article presents the complete results of the study. The samples have proven to be extremely useful to participants and have led to a number of publications in which new advances and approaches in organic depth profiling have been demonstrated 18–21. The reference materials have already provided insight into fundamental aspects of organic depth profiling, such as the dose and energy dependence of the sputtering yield, the depth resolution, sputter‐induced roughening and molecular secondary ion behavior.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the amount of chemical damage from C 60 + sputtering is strongly dependent on the incidence angle for PS and polycarbonate (PC). [14] Yu et al [9] reported the use of co-sputtering of C 60 + and low energy monoatomic Ar + ions to achieve a constant sputter rate and a successful SDP of multiple organic thin films in a model organic light-emitting diode (OLED). It was suggested that success of the cosputtering technique was based on the Ar + ion beam breakage of crosslinking bonds in the organic film and the reduction of amorphous carbon depositing on the surface during the SPD.…”
Section: Introductionmentioning
confidence: 99%
“…Previous experiments using C 60 + and coronene cluster ions have not been successful for obtaining a chemical SPD of a PI surface. [14] Attempts to use the cosputtering procedure [9] were also not successful with PI. In these experiments, the sputtered PI surfaces showed compositional damage with decreased nitrogen and oxygen atomic concentrations as well as a chemical degradation in the nitrogen bonding chemistry.…”
Section: Introductionmentioning
confidence: 99%